2022
DOI: 10.3390/healthcare10102019
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Interventions in Depression Care—A Survey on Acceptance from the Perspective of Patients, Their Relatives and Health Professionals

Abstract: Digital health interventions may contribute to closing the treatment gap for depression by reaching large populations at relatively low costs. This article presents the results of a broad, multisided German survey in 2020 on the acceptance and use of digital health interventions in depression care from the perspective of patients, their relatives, and health professionals. A total of 97 patients and relatives and 229 health professionals participated. Survey participants reported openness towards the use of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Also, self-reported competence and actual behaviour may differ in practical situations. Another interpretation of this finding could be that digital skills have a minor role for participants: Previous research on patients' mobile health adoption identified users' self-efficacy as an essential component for digital mental health interventions adoption ( 19 , 46 , 60 , 61 ). Taken together, this suggests that patients tend to perceive digital skills as a small hurdle if they are convinced they may benefit from DTx.…”
Section: Discussionmentioning
confidence: 98%
“…Also, self-reported competence and actual behaviour may differ in practical situations. Another interpretation of this finding could be that digital skills have a minor role for participants: Previous research on patients' mobile health adoption identified users' self-efficacy as an essential component for digital mental health interventions adoption ( 19 , 46 , 60 , 61 ). Taken together, this suggests that patients tend to perceive digital skills as a small hurdle if they are convinced they may benefit from DTx.…”
Section: Discussionmentioning
confidence: 98%
“…One study in particular did not allow for single attribution of information to the group of healthcare professionals. 16 And due to the different study designs, different medical conditions and subjective selection of questions in interviews and surveys may bias the results, especially as some studies focus on special DHAs that include special features and obstacles not transferable to all kinds of DHAs. Some studies incorporated service providers that already had experience with DHAs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the main reason for refusal was financial. In a survey of patients with depression [ 20 ], the fact that all costs are covered is a factor that facilitates acceptance. Our results may differ from those in other countries, such as Germany or the United States, where Deprexis is reimbursed when prescribed by a health care professional.…”
Section: Discussionmentioning
confidence: 99%